Effects of endurance training combined with blood flow restriction on functionality in older adults: a systematic review - Roque Santos de Oliveira; Renato Gouveia Borgonove; Maria Luiza de Jesus Miranda; Gilberto Candido Laurentino (Brazilian Society of Geriatrics and Gerontology, 2024)
The aim of this review was to verify the effects of aerobic exercise combined with blood flow restriction on older adult functionality. Systematic searches were performed in PubMed, Web of Science, and Embase between July and December 2023. Randomized studies with participants aged ≥ 60 years who were evaluated before and after the experimental protocols were included. We registered this systematic review at the International Prospective Register (PROSPERO CRD42022347205). The search strategy identified 2698 studies, four of which were included in the review, with 80 participants. The results suggested that aerobic exercise combined with blood flow restriction increased performance on specific functional tests. However, these results should be interpreted with caution due to the low-to-moderate study quality, as well as the low number of participants and studies. In conclusion, aerobic exercise and blood flow restriction may increase functional capacity in older adults. Further studies are needed to confirm such findings.